Expression of Nitric Oxide Synthase Isoenzyme in Lung Tissue of Smokers with and without Chronic Obstructive Pulmonary Disease - Jiang, Wen-Ting (Chin Med J (Engl), 2015)
BACKGROUND: It has been demonstrated that only 10%–20% cigarette smokers finally suffer chronic obstructive pulmonary disease (COPD). The underlying mechanism of development remains uncertain so far. Nitric oxide (NO) has been found to be closely associated with the pathogenesis of COPD, the alteration of NO synthase (NOS) expression need to be revealed. The study aimed to investigate the alterations of NOS isoforms expressions between smokers with and without COPD, which might be helpful for identifying the susceptibility of smokers developing into COPD. METHODS: Peripheral lung tissues were obtained from 10 nonsmoker control subjects, 15 non-COPD smokers, and 15 smokers with COPD. Neuronal NOS (nNOS), inducible NOS (iNOS), and endothelial NOS (eNOS) mRNA and protein levels were measured in each sample by using real-time polymerase chain reaction and Western blotting. RESULTS: INOS mRNA was significantly increased in patients with COPD compared with nonsmokers and smokers with normal lung function (P < 0.001, P = 0.001, respectively). iNOS protein was also higher in COPD patients than nonsmokers and smokers with normal lung function (P < 0.01 and P = 0.01, respectively). However, expressions of nNOS and eNOS did not differ among nonsmokers, smokers with and without COPD. Furthermore, there was a negative correlation between iNOS protein level and lung function parameters forced expiratory volume in 1 s (FEV(1)) (% predicted) (r = −0.549, P = 0.001) and FEV(1)/forced vital capacity (%, r = −0.535, P = 0.001). CONCLUSIONS: The expression of iNOS significantly increased in smokers with COPD compared with that in nonsmokers or smokers without COPD. The results suggest that iNOS might be involved in the pathogenesis of COPD, and may be a potential marker to identify the smokers who have more liability to suffer COPD.